PENERAPAN ARSITEKTUR KONTEMPORER PADA PERANCANGAN ISLAMIC CENTER DI KOTA SOLO - Rosyid Amirul Ardli; Anggraeni Dyah Sulistiowati; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
Islamic Center has the meaning of a physical container that accommodates several Islamic activities and supports. Among these activities consist of worship activities, mu'amalah and da'wah. The Islamic Center also has a role as a center for Islamic information both for Muslims and for people who want to know and want to learn about Islam. Therefore, with the design of an Islamic Center Area, it is hoped that it can accommodate community activities in the fields of religious education, economics and sports and can respond to the need for open space in the city of Solo. The Islamic Center area applies the concept of Contemporary Architecture as an effective form of approach to the surrounding community, especially for teenagers. Keywords: Islam, Center for Religious Activities, Religious Tourism, Solo.